08.02 Alpha-enolase promotes pro-inflammatory phenotype of monocytes-derived macrophages in vitro. (1st March 2017) - Fréret, Manuel; Rottenberg, Pascal; Calbo, Sébastien; Lequerré, Thierry; Vittecoq, Olivier
Abstract : Background: Rheumatoid arthritis (RA) is the most common chronic inflammatory rheumatism. RA is multifactorial involving genetic, environmental, endocrine, psychological and immunological factors. In 2002, our research team has discovered alpha-enolase (ENO1) as an autoantigen in RA and has recently demonstrated its effect on monocytes, inducing inflammation mediated through CD14-dependent TLR4 signalling pathway. Monocytes can differentiate into dendritic cells, osteoclasts or macrophages. Macrophages are involved in RA pathophysiology and can be polarised in different phenotypic profiles, pro-inflammatory (M1 macrophages) or immuno-regulatory (M2 macrophages). The main objective of this study was to determine the effect of ENO1 on monocytes differentiation into macrophages and on their polarisation. Materials and methods: Monocytes of healthy donors were cultured with M-CSF (Macrophage-Colony Stimulating) or GM-CSF (Granulocyte Macrophage-Colony Stimulating Factor) for 5 days for their differentiation into macrophages and for 3 supplemental days with IFN-γ and/or LPS or IL-4 and/or IL-10 for M1 or M2 polarisation respectively. Monocytes and monocytes-derived macrophages were also cultured with recombinant ENO1 (produced in E. coli ), or control BSA, to investigate its effect on monocytes differentiation and macrophages polarisation. Microscopy, flow cytometry and ELISA were performed to determine the macrophages polarisation profile (M1 or M2) induced by ENO1. Results: Firstly, we showed that ENO1 did not induce monocytes differentiation into macrophages in contrast to M-CSF and GM-CSF. However, in macrophages differentiated with M-CSF or GM-CSF, ENO1 induces M1 polarisation in terms of morphology, surface markers and cytokines production. ENO1 can also initiate repolarization in M1 of macrophages previously polarised in M2. Finally, we showed that ENO1 induced a cytokine inflammatory response higher in macrophages differentiated with GM-CSF compared to M-CSF. Conclusions: These results showed for the first time the potential role of native ENO1 in the inflammatory process of RA through its interaction with macrophages, promoting their polarisation into pro-inflammatory M1 profile. Our project, aimed to understand the role ENO1 in RA pathophysiology, opens interesting research perspectives on cell types derived from monocytes.